Changes in children's surgical services during the COVID-19 pandemic at a tertiary-level government hospital in a lower middle-income country - Tanvir Kabir Chowdhury; Md. Afruzul Alam; Md. Abdullah Al Farooq; S M Humayun Kabir; Ayesha Sadia; Tanzil Farhad (BMJ Publishing Group, 2021)
Objective The aim of this study was to quantify the changes that occurred in the surgical services of children during the COVID-19 pandemic from the perspective of a low/middle-income country.Design A case-control study was conducted at a large referral centre in Bangladesh among patients aged ≤12 years. Comparisons were made between cases admitted during a period of 'April to September 2020' (Pandemic period) and controls during a similar period in 2019 (Reference period). The number of admissions and outpatient department (OPD) attendances, age and sex distribution, diagnosis, number and types of surgeries performed (elective vs emergency), variations in treatment of acute appendicitis, types of anaesthesia and mortality were compared.Results Admissions were only 41% of previous year (635 vs 1549), and OPD attendances were only 28% of previous year (603 vs 2152). Admission of children reduced by 65.8%, but neonatal admission reduced only by 7.6%. The median age of the admitted patients was significantly lower during the pandemic period (3 vs 4 years, p<0.01). Acute appendicitis (151, 9.8%) and trauma (61, 9.6%), respectively, were the the most common causes of admission during the reference and the pandemic period. Elective surgeries were only 17% and emergency surgeries were 64% of previous year (p<0.01). Appendectomy (88, 9.1%) and laparotomy (77, 17.6%), respectively, were the most common surgeries performed during the reference and the pandemic period. Conservative treatment of acute appendicitis was more during the pandemic period (47.5% vs 28.5%, p=0.01), but patients who underwent appendectomies had more complicated appendicitis (63.3% vs 42.1%, p=0.01). In all, 90.4% of surgeries were performed by resident doctors. There were no COVID-19- related deaths.Conclusion Trauma became the most common cause of admission during the pandemic, and neonatal surgical conditions remained almost unchanged with high mortality rates. Elective procedures and laparoscopy remained low and resident doctors played a major role in providing surgical services.